Bridging the Gap: Navigating Regulations to Enhance Referral Coordination Between Puskesmas and Hospitals - Malia Fadhilah , Isna Najwa; Firdausy, Amala Hessa; Savira , Berliana Hanza; Zalianti , Devina Amelia; Sefriza , Ayla; Ayu Hastari, Findi Vinolia; Rahmadyanti , Rosalya Galuh; Harianja, Ardisa Larassati; Khairani , Ghefira Nayana (Tarqabin Nusantara Group, 2025)
Referral coordination between community health centers (Puskesmas) and hospitals is critical for ensuring seamless healthcare delivery, yet it remains hindered by regulatory challenges. This study explores the dual role of regulations in either supporting or impeding referral systems, focusing on payment mechanisms, legal frameworks, technological integration, and socioeconomic barriers. Supportive regulations, such as service payment contracts, government subsidies, and integrated information systems, enhance efficiency and collaboration. However, anti-kickback laws, fragmented systems, and lack of standardized criteria often create inefficiencies and inequitable access. Addressing these issues requires policy reforms, investment in technology, and targeted interventions to overcome socioeconomic barriers. Evidence suggests that strengthening Puskesmas as gatekeepers, adopting value-based payment models, and leveraging telemedicine can significantly improve referral outcomes. By aligning regulations with collaborative care objectives, healthcare systems can achieve better patient outcomes, reduce costs, and promote equitable access to specialty care. This analysis underscores the urgent need for systemic reforms to bridge gaps and optimize referral coordination.